EXPLORING ENGLISH LANGUAGE EXPOSURE TO STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM UNIVERSITAS NEGERI GORONTALO - Elma Jilan Akili; Indri Wirahmi Bay, Sri Widyarti Ali (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Language proficiency is a critical skill, and understanding the dynamics of language exposure is fundamental to its acquisition. This research applied quantitative descriptive research aims to describe language exposure among 2021 English Department students at the English Language Education Study Program (ELESP), Universitas Negeri Gorontalo. The study is guided by Magno's exposure framework, encompassing home, friends, school, and media. The background of the study highlights the importance of language exposure in language acquisition, with a specific focus on the four exposure types within the context of ELESP. The objectives centre on providing information about the language exposure experiences of the 2021 cohort, guided by these four exposure types. The methodology employs a quantitative descriptive approach, using surveys and written interviews. The practical significance of this study lies in its potential use as a resource for ELESP, offering insights into the effectiveness of their English language exposure across these four types. Theoretically, the research contributes to the academic discourse, serving as a learning resource for students of ELESP and offering a new perspective for future researchers in the same field.